Impact of nutrition on inflammation, tauopathy, and behavioral outcomes from chronic traumatic encephalopathy - Yu, Jin (J Neuroinflammation, 2018)
BACKGROUND: Repetitive mild traumatic brain injuries (rmTBI) are associated with cognitive deficits, inflammation, and stress-related events. We tested the effect of nutrient intake on the impact of rmTBI in an animal model of chronic traumatic encephalopathy (CTE) to study the pathophysiological mechanisms underlying this model. We used a between group design rmTBI closed head injuries in mice, compared to a control and nutrient-treated groups. METHODS: Our model allows for controlled, repetitive closed head impacts to mice. Briefly, 24-week-old mice were divided into five groups: control, rmTBI, and rmTBI with nutrients (2% of NF-216, NF-316 and NF-416). rmTBI mice received four concussive impacts over 7 days. Mice were treated with NutriFusion diets for 2 months prior to the rmTBI and until euthanasia (6 months). Mice were then subsequently euthanized for macro- and micro-histopathologic analysis for various times up to 6 months after the last TBI received. Animals were examined behaviorally, and brain sections were immunostained for glial fibrillary acidic protein (GFAP) for astrocytes, iba-1 for activated microglia, and AT8 for phosphorylated tau protein. RESULTS: Animals on nutrient diets showed attenuated behavioral changes. The brains from all mice lacked macroscopic tissue damage at all time points. The rmTBI resulted in a marked neuroinflammatory response, with persistent and widespread astrogliosis and microglial activation, as well as significantly elevated phospho-tau immunoreactivity to 6 months. Mice treated with diets had significantly reduced inflammation and phospho-tau staining. CONCLUSIONS: The neuropathological findings in the rmTBI mice showed histopathological hallmarks of CTE, including increased astrogliosis, microglial activation, and hyperphosphorylated tau protein accumulation, while mice treated with diets had attenuated disease process. These studies demonstrate that consumption of nutrient-rich diets reduced disease progression.